Pre-Assessment of Transtibial Prosthetic Pylon Using Auxetic Bowtie Model: A Simulation and Experimental Validation - Lenggana, Bhre Wangsa; Fardan, Muhammad Faris; Ubaidillah; Choi, Seung-Bok; Susilo, Didik Djoko; Khan, Sohaib Zia; Zaidi, Asad Ali (Engineering, Technology & Applied Science Research, 2026)
In the present study, a prosthetic device is designed to function as a replacement for a missing limb. This device typically consists of suspension, liner, socket, pylon, and foot components. The research objectives are to design a pylon component for transtibial prosthetics by implementing auxetic metamaterials and to validate the performance of the designed pylon under quasi-static and dynamic conditions. The design and analysis processes were conducted with Finite Element Analysis (FEA), and its effectiveness was validated through experimental testing of the prototype pylon sample. In the design process, the pylon structure is formulated by rearranging the Two-Dimensional (2D) re-entrant hexagon model into a Three-Dimensional (3D) model. The design evaluation identified that the pylon exhibits a stiffness of 1404 kN/mm, 4680 kN/mm, and 9360 kN/mm for the 0.3 mm, 1 mm, and 2 mm thick ligaments, respectively. It was found that a pylon with a 0.3 mm-thick ligament caused a deformation (S) of 0.53 cm during a single period of the gait cycle, while a 1 mm-thick ligament caused an S of 0.4 cm. It was also found from the S transition of the primary and secondary bends that a negative Poisson’s ratio occurred in the 3D model transformed from a 2D re-entrant hexagon.